Canadian History Blogging: Reflections at the Intersection of Digital Storytelling, Academic Research, and Public Outreach - Adcock, Tina; Grant, Keith; Nation-Knapper, Stacy; Robertson, Beth; Slumkoski, Corey (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2016)
This article surveys the impacts of blogging on Canadian historical practice to date. Drawing upon the experiences and practices of five collaborative or multi-author Canadian history blogs — ActiveHistory.ca, The Otter~La Loutre, Findings/Trouvailles, the Acadiensis Blog, and Borealia — it explores how this activity is changing the ways in which Canadian historians tell stories, publish their research, teach, and serve academic and wider communities. Blogging has encouraged new forms of historical storytelling and the inclusion of underrepresented and marginalized voices in public discussions of Canadian historical narratives. It is being integrated into cycles of academic publication and undergraduate and graduate classrooms. Yet challenges remain with regard to determining the place and value of blogging within standard paradigms of academic labour. As more Canadian historians come to read, write for, and edit historical blogs, however, they will not only help shift the practice of Canadian history inside and outside university campuses, but will also experience the pleasures and rewards of this kind of digital historical work for themselves.